The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1161/01.hyp.11.2_pt_2.i57
|View full text |Cite
|
Sign up to set email alerts
|

Brain renin-angiotensin. Central control of secretion of atrial natriuretic factor from the heart.

Abstract: HIROSHI ITOH, KAZUWA NAKAO, TAKAYUKI YAMADA, NARITO MORE, SHOZO SHIONO, AKIRA SUGAWARA,. YOSHMKO SAJTO, MASASHI MUKOYAMA, HIROSHI ARAI, AND HIROO IMURASUMMARY To elucidate the modulatory role of the brain renln-angiotensin system in the regulation of the secretion of atrial natriuretic factor (ANF) from the heart, the effects of intracerebroventricular administration of angiotensin II on the plasma ANF level were examined in conscious unrestrained rats. Administration of angiotensin II in doses of 100 ng and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In dogs, Edward et al (23) noted that Ang II infusion increased circulating ANP concentrations. Itoh et al (24) infused Ang II icy into rats and found that under these circumstances the release of ANP in response to saline loads was increased. However, the Ang II-icy was given acutely rather than chronically in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, Edward et al (23) noted that Ang II infusion increased circulating ANP concentrations. Itoh et al (24) infused Ang II icy into rats and found that under these circumstances the release of ANP in response to saline loads was increased. However, the Ang II-icy was given acutely rather than chronically in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence includes 1) the threshold of the centrally mediated dipsogenic response to Ang II is lower than the pressor response 11 and 2) the brain renin-angiotensin system has been reported to control the release of atrial natriuretic factor, a hormone clearly implicated in volume regulation. 12 Ang II administered centrally, however, releases vasopressin, which has been reported to produce greater pressor effects in male than in female rats. 13 The effects of plasma supernate of dogs on the Na + -K + pump activity of the rat tail artery was independent of gender.…”
Section: Discussionmentioning
confidence: 98%
“…11B). 8,9,5965) Furthermore, the natriuretic peptide system has therapeutic implications for vascular regeneration in patients with arteriosclerosis obliterans. 48)…”
Section: Translational Research On Endocrinology and Metabolismmentioning
confidence: 99%